PEMANFAATAN KELAPA DALAM MEWUJUDKAN KEMANDIRIAN EKONOMI MASYARAKAT DESA BEANENO KECAMATAN SASITAMEAN KABUPATEN MALAKA - Cornelius Efraim Pen Timung; Veronika Ina Assan Boro; Yohana Fransiska mehdo (Journal Education and Government Wiyata, 2026)
This study aims to analyze the utilization of coconut in realizing the economic independence of the people of Beaneno Village, Sasitamean District, Malaka Regency. The research used a qualitative descriptive method with a community empowerment approach based on local potential. Data collection techniques were carried out through observation, in-depth interviews, and documentation involving village governments, farmer groups, coconut farmers, and local communities as research informants. The results showed that the utilization of coconut in Beaneno Village has become an important instrument in encouraging community economic independence through the formation of farmer groups, copra processing, and collective marketing of coconut products. Community independence is reflected through the community’s ability to form coconut commodity management organizations, create household-based employment opportunities, and develop a mutual cooperation business management system. Community empowerment is carried out through increasing knowledge about coconut cultivation, coconut product processing, and increasing community awareness of the economic potential of coconut commodities. The involvement of the village government can be seen through support for the provision of land, seeds, fertilizers, and the establishment of farmer groups as a form of village institutional intervention in strengthening the local economy. Theoretically, this study shows that community empowerment based on locality is able to strengthen the economic capacity of rural communities through productive and sustainable utilization of local natural resources.